The Social Responsiveness Scale (SRS) in the Valuation of Social Skills in Music and Music Therapy research: A literature review - Ingeborg, Haering Sylvia (European Journal of Social Science Education and Research, 2025)
This literature review seeks to find out, if the Social Responsiveness Scale (SRS) could be a useful instrument in an inclusive scholastic context when music therapy-based interventions are applied. The aim is to compare studies in which the SRS is a used to measure the impact of music-based interventions, and to deduce its usability in an inclusive scholastic context. Literature research on the databases RomaTreDiscovery, Science Direct, Google Scholar, PubMed, and Cochrane is conducted the 28.07.2017 and the 08.08.2017 using the keywords “social responsiveness scale”, “autism”, and “music”. The following inclusion criteria are applied: the studies are either randomized controlled trials (RCT) or controlled trials (CT), use the SRS as outcome measure, utilize a music-based intervention, and target a population of children or adolescents with ASD. During the literature research 11 studies were identified, based on title and abstract. After studying the full articles 4 met the inclusion criteria (Bhatara et al., 2009; Geretsegger et al., 2012;  La Gasse, 2014; Thompson, McFerran & Gold, 2013). An analysis aiming on the type of the music intervention, the population, and the frequency of interventions is conducted. Since the number of studies that met the inclusion criteria is rather small, there is only little evidence from this research. Since the SRS seems to be a useful tool confronting the influence of music on social skills in children and adolescents, it might be applicable to measure the impact of music therapy in an inclusive classroom.
Keywords: Social Responsiveness Scale, music intervention, music therapy, inclusion